KAJIAN PERAN DESA DALAM PERLINDUNGAN DAN PEMBERDAYAAN PEREMPUAN DAN ANAK - Emi Hidayati (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2018)
This study aims to describe the role of the government in the village of women empowerment and child protection. This study sought to measure what it does and that is not the Government of the village close to Government targets in support of Banyuwangi Regency related issues of women empowerment and child protection based on the perspective of public policy. Type of this research is descriptive-qualitative approach uses. The role of the village in the empowerment of women and protection of children in other countries still need to have the support of the various parties are still weak because of the role of terkaiit village in the empowerment of women and children. The Government funds the village to permberdayaan women and child protection in addition to the still minimal, yet can drive civil society organisations to be able to participate in women's empowerment and child protection.